2015
DOI: 10.1007/s13277-015-4281-6
|View full text |Cite
|
Sign up to set email alerts
|

GALNT7, a target of miR-494, participates in the oncogenesis of nasopharyngeal carcinoma

Abstract: GalNAc-transferase-7 (GALNT7) is essential for the regulation of cell proliferation and has been implicated in tumorigenesis. However, the role of GALNT7 in the development and progression of nasopharyngeal carcinoma (NPC) remains unclear. Our previous study showed that GALNT7 was a putative target of miR-494, which was confirmed by luciferase reporter assay. In the present study, we demonstrated that in vitro knockdown of GALNT7 significantly inhibited the proliferation, colony formation, migration, and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The expression level of GALNT7 was dramatically decreased in SiHa and Caski cells after overexpression of miR-30e. It has been reported that GALNT7 plays a role in carcinogenesis and metastasis in many common cancers [30] , [37] . Meanwhile, GALNT7 is found to be upregulated in cancers such as laryngeal carcinoma and cervical cancer [36] , [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression level of GALNT7 was dramatically decreased in SiHa and Caski cells after overexpression of miR-30e. It has been reported that GALNT7 plays a role in carcinogenesis and metastasis in many common cancers [30] , [37] . Meanwhile, GALNT7 is found to be upregulated in cancers such as laryngeal carcinoma and cervical cancer [36] , [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The O-glycosylation of these glycoproteins is considered to play a key role in determining tumor properties in many cases of cancer, such as cervical cancer, hepatocellular carcinoma, and esophageal squamous cell cancer [17] , [28] , [29] . It has been reported that GALNT7 was targeted by some of miRNAs, such as miR-214, miR-494, and miR-17, in different cancers [17] , [28] , [30] . However, the expression and the regulation of GALNT7 in cervical cancer remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of O-glycosylation Identified as oncogene in several types of cancer and controlled by micro-RNAs (Gaziel-Sovran et al , Peng et al 2012, Li et al 2014b, Nie et al 2015, Lu et al 2016 Upregulated in malignant PCa as part of a glycosylation gene signature (Barfeld et al 2014a). Androgen regulated and linked to prostate cancer cell viability ) GCNT1…”
Section: :3mentioning
confidence: 99%
“…Potential biomarker in colorectal cancer . Linked to survival and invasion in lung cancer (Fujita et al 2015) Not reported Nie et al 2015, Lu et al 2016 and is upregulated in malignant prostate cancer as part of a glycosylation gene signature (Barfeld et al 2014a). As GALNT7 initiates O-glycosylation, upregulation of this enzyme could be linked to a range of changes to O-glycans in prostate cancer cells.…”
Section: :3mentioning
confidence: 99%
“…21 However, the role of miR-494-3p in NPC remains unclear, though there were studies reported the functional evidence of miR-494 in the tumorigenesis of NPC. 22 , 23 To better characterize how the altered expression of miR-494-3p might contribute to NPC development, we examined the expression levels of miR-494-3p in NPC and analyze its impacts on the biological functions of NPC cells.…”
Section: Introductionmentioning
confidence: 99%